PERSIDANGAN PERKARA PIDANA ONLINE DALAM KAITANNYA DENGAN HUKUM PEMBUKTIAN DI PENGADILAN NEGERI POSO - Jimmy Donovan; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (Universitas Dharmawangsa, 2023)
ABSTRACTThe concept of proof in online criminal trials in early research is often echoed thatevidence tends to be a formality, even though detention is carried out. So that tends to bein online crime, the defendant/legal adviser cannot verify and identify the evidencesubmitted by the public prosecutor. While the evidence determines the truth whether thedefendant committed a crime or not. To find out the concept of implementing onlinecriminal justice during the Covid-19 period, as well as how to get around the obstacles andsolutions carried out by the Poso District Court regarding the concept of proof during theCovid 19 pandemic, it is necessary to conduct research. The results of the study foundthat in the context of proof it is necessary to maintain the system evidence in the contextof fulfillment of the nature of material truth. In order to get around the obstacles within thescope of the Poso District Court where the obstacles to fulfilling the principle of trials thatare open to the public as well as technical obstacles within the scope of HumanResources in the legal structure system, it is necessary to complete the fulfillment ofelements in Technology and Information Personnel. To maximize the costs incurred thefulfillment strategy will be borne by the defendant.Keywords: Trial; Criminal Cases; Online; Poso District Court.